A Switchable Solvent-Based Liquid Phase Microextraction Method for the Detection of Cadmium in Water Samples with Flame Atomic Absorption Spectrometry - AYDIN URUCU, OYA (OXFORD UNIV PRESS INC, 2021)
Background: The natural concentration of trace elements in water and soil depends on the geological, geomorphological, and climate characteristics of the region. The rapid increase of technology in recent years has increased concentrations of trace elements in nature. Objective: Separation and enrichment methods are needed to detect trace amounts of heavy metals that cannot be detected due to the detection limit of the instruments or the matrix effect in samples. Recently, low hazard solvents compatible with green chemistry have been used in preconcentration/separation studies of Cd(II). Methods: Switchable solvent-based liquid phase microextraction is an environmentally-friendly, simple, and fast procedure for the determination of Cd(II) ions in environmental samples combined with flame atomic absorption spectrometry (FAAS). Results: he switchable polarity solvent was prepared with N,N-dimethyl-n-octylamine. 2-(5-Bromo-2-pyridylazo)-5-(diethylamino) phenol was used as the complexing agent. Important parameters such as pH, amount of switchable polarity solvent and NaOH, as well as ligand and sample volume, all of which might affect the microextraction efficiency were optimized. Under optimal experimental conditions, linear range was found to be between 5 and 500 mu g/L. The limit of detection, preconcentration factor, and relative standard deviation were 0.89 mu g/L, 150, and 3.2%, respectively. Highlights: The accuracy of our method was confirmed by the analysis of certified reference material SPS-WW1 Batch 106 (Waste Waters). The developed procedure was successfully applied to determine the cadmium contents of environmental water samples. We believe that this environmentally-friendly method will be useful in detecting Cd(II) ions in water samples.
Keywords: ORGANIC DROP MICROEXTRACTION; ULTRA-TRACE DETECTION; HOLLOW FIBER; METAL-IONS; EXTRACTION; PRECONCENTRATION; FOOD; COPPER(II); OPTIMIZATION; SEPARATION